Pulsed laser deposition of Sr2FeMoO6 thin films grown on spark plasma sintered Sr2MgWO6 substrates. (16th May 2017) - Santosh, M; Lacotte, M; David, A; Boullay, Ph; Grygiel, C; Pravarthana, D; Rohrer, G S; Salvador, P A; Padhan, P; Lüders, U; Wang, Junling; Prellier, W
Abstract: Sr2 FeMoO6 (SFMO) films were deposited on polycrystalline spark plasma synthesized Sr2 MgWO6 (SMWO) substrates. Films were grown using pulsed laser deposition at temperatures ( T dep ) between 720 °C and 820 °C in a vacuum environment of pressure P d e p = 10 − 6 mbar (0.1 mPa); after deposition they were cooled either in a pressure P c o o l = P d e p or P c o o l = 10 − 4 mbar (10 mPa) O2 . Despite the use of an isostructural substrate, the growth and cooling conditions play the primary role in determining details of the films' structures and properties, similarly to single-crystals. Grazing x-ray and electron back-scatter diffraction indicate that vacuum-cooled films were pure perovskite-structured SFMO exhibiting grain-over-grain growth that aligned the perovskite sub-cells. SrMoO4 impurities were observed in the x-ray patterns for the oxygen-cooled films similarly to single-crystal substrates. Magnetic, electronic and magnetoresistive properties were all a function of growth and cooling environments. The Curie temperature and magnetization of the films increased with T dep up to 800 °C. The vacuum-cooled films had low-resistivities with essentially metallic conductivity (small resistivity increases occurred at low-T), while the conductivity of oxygen-cooled films were consistent with variable range hopping. The oxygen-cooled films had higher low-field magnetoresistance effects at 5 K than the vacuum-cooled films, which seems consistent with SrMoO4 forming at grain boundaries. This work opens the route to tailor the electronic properties by engineering the grain boundaries in thin films.